2004
DOI: 10.1890/03-8024
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Limitation of Plant Reproduction: Ecological and Evolutionary Causes and Consequences

Abstract: Determining whether seed production is pollen limited has been an area of intensive empirical study over the last two decades. Yet current evidence does not allow satisfactory assessment of the causes or consequences of pollen limitation. Here, we critically evaluate existing theory and issues concerning pollen limitation. Our main conclusion is that a change in approach is needed to determine whether pollen limitation reflects random fluctuations around a pollen-resource equilibrium, an adaptation to stochast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
1,158
8
26

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,138 publications
(1,217 citation statements)
references
References 83 publications
25
1,158
8
26
Order By: Relevance
“…Thus, the attraction of both pollinators and cucumber beetles is likely to have fitness consequences for native cucurbits and implications for crop yield in managed cucurbit systems. While a growing number of studies have demonstrated that floral display or reward can be costly due to the attraction of antagonists (Brody and Mitchell 1997;Adler and Bronstein 2004;Ashman et al 2004b;Strauss and Irwin 2004), the current study is one of few to address the role of scent in attracting pollinators compared to herbivores. Similar to our study, specific floral volatiles present in C. arvense scent attracted just pollinators, just herbivores, or both pollinators and herbivores (Theis 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the attraction of both pollinators and cucumber beetles is likely to have fitness consequences for native cucurbits and implications for crop yield in managed cucurbit systems. While a growing number of studies have demonstrated that floral display or reward can be costly due to the attraction of antagonists (Brody and Mitchell 1997;Adler and Bronstein 2004;Ashman et al 2004b;Strauss and Irwin 2004), the current study is one of few to address the role of scent in attracting pollinators compared to herbivores. Similar to our study, specific floral volatiles present in C. arvense scent attracted just pollinators, just herbivores, or both pollinators and herbivores (Theis 2006).…”
Section: Discussionmentioning
confidence: 99%
“…When studying the impact of land‐use change and disturbance, it is of particular importance to understand whether organisms that perform important ecosystem services persist in human‐dominated ecosystems. Pollinators are one such group: Most of the world's flowering plants require animal pollinators (Ashman et al., 2004), and plant populations in human‐dominated ecosystems will only maintain genetic diversity if pollinators are present and can move freely through anthropogenic habitats (Keller & Waller, 2002). Bees are key providers of pollination services, which are vital for crop production and food security and the persistence of many wild plants (Klein et al., 2007; Ollerton, Winfree, & Tarrant, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Plant-pollinator interactions and the reproductive outcome of such mutualisms are central to plant population and community organization (Ashman et al 2004). For this reason, these topics have been intensively studied in a variety of contexts (Ayasse & Arroyo 2011).…”
Section: Introductionmentioning
confidence: 99%